Slip distribution of the 2017 Mw6.6 Bodrum-Kos earthquake: resolving the ambiguity of fault geometry - Konca, A. Ozgun; Guvercin, Sezim Ezgi; Ozarpaci, Seda; Ozdemir, Alpay; Funning, Gareth J.; Dogan, Ugur; Ergintav, Semih; Floyd, Michael; Karabulut, Hayrullah; Reilinger, Robert (OXFORD UNIV PRESS, 2019)
The 2017 July 20, M(w)6.6 Bodrum-Kos earthquake occurred in the Gulf of Gokova in the SE Aegean, a region characterized by N-S extension in the backarc of the easternmost Hellenic Trench. The dip direction of the fault that ruptured during the earthquake has been a matter of controversy where both north- and south-dipping fault planes were used to model the coseismic slip in previous studies. Here, we use seismic (seismicity, main shock modelling, aftershock relocations and aftershock mechanisms using regional body and surface waves), geodetic (GPS, InSAR) and structural observations to estimate the location, and the dip direction of the fault that ruptured during the 2017 earthquake, and the relationship of this event to regional tectonics. We consider both dip directions and systematically search for the best-fitting locations for the north- and south-dipping fault planes. Comparing the best-fitting planes for both dip directions in terms of their misfit to the geodetic data, proximity to the hypocenter location and Coulomb stress changes at the aftershock locations, we conclude that the 2017 earthquake ruptured a north-dipping fault. We find that the earthquake occurred on a 20-25 km long, similar to E-W striking, 40. north-dipping, pure normal fault with slip primarily confined between 3 and 15 km depth, and the largest slip exceeding 2m between depths of 4 and 10 km. The coseismic fault, not mapped previously, projects to the surface within the western Gulf, and partly serves both to widen the Gulf and separate Kos Island from the Bodrum Peninsula of SW Anatolia. The coseismic fault may be an extension of a mapped, north-dipping normal fault along the south side of the Gulf of Gokova. While all of the larger aftershocks are consistent with N-S extension, their spatially dispersed pattern attests to the high degree of crustal fracturing within the basin, due to rapid trenchward extension and anticlockwise rotation within the southeastern Aegean.
Keywords: Satellite Geodesy; Europe; Earthquake source observations; Seismicity and tectonics; SOUTHWEST ANATOLIA; HECTOR MINE; AEGEAN SEA; EVOLUTION; CALIFORNIA; INVERSION; NETWORK; REGION; GOKOVA; GULF; Geochemistry & Geophysics